gH625-liposomes deliver PACAP through a dynamic in vitro model of the blood–brain barrier - Barra, Teresa; Falanga, Annarita; Bellavita, Rosa; Laforgia, Vincenza; Prisco, Marina; Galdiero, Stefania; Valiante, Salvatore (Frontiers in Physiology, 2022)
The blood brain barrier (BBB) selectively protects the central nervous system (CNS) from external insults but its function can represent a limit for the passage of therapeutic molecules. Numerous in vitro models of the BBB have been realized in order to study the passage of drugs for neurodegenerative diseases, but these in vitro models are not very representative of the physiological conditions because of a limited supply of oxygen and nutrients due to static conditions. To avoid this phenomenon, we used a millifluidic bioreactor model that ensures a circulation of the medium and therefore of the nutrients thanks to the continuous laminar flow. This dynamic model consists of a double culture chamber separated by a membrane on which brain endothelial cells are cultured in order to evaluate the passage of the drug. Furthermore, in the lower chamber SH-SY5Y were seeded as 3D spheroids to evaluate the drug passage through these cells. As nanodelivery system, we used liposomes functionalized with viral fusion peptide to evaluate the passage of a neuroprotective agent, pituitary adenylate cyclase-activating polypeptide (PACAP) through the dynamic in vitro model of BBB. We showed that our nanodelivery system, made by functionalized liposomes and loaded with specific molecule, efficiently crosses the in vitro fluid-dynamic model of BBB. Our findings represent an important step to further experimental investigations on PACAP administration as a therapeutic agent by enhanced drug delivery system. Our results can improve the diffusion of good practice in neuroscience laboratories helping to spread the 3R rules.